APLIKASI MUDHARABAH DALAM PERBANKAN SYARIAH DI INDONESIA - Suryaningsih, Sri Abidah (Journal of Innovation in Business and Economics, 2013)
This theory analysis article aims to describe the meaning of mudharabah, explain about Sharia banks, and provide an overview on implementation of mudharabah in Islamic banking in Indonesia. Mudharabah takes place when there are investor (Shahibul mall), fund manager (mudharib), business activity, and profit sharing proportion (nisbah) agreement between investor and manager. Sharia banking should be performed based on some characteristics, specifically: usury (riba)-free, provides public services and realizes the socio-economic goals of Islam, universal, and applies profit and loss sharing. Moreover, mudharabah application in Islamic banking in Indonesia has the following characteristics: transactions must be intended to financing, business management is entrusted to mudhorib, and profits sharing system must be based on the principle of revenue sharing and proportion of profit sharing are subject to change during the term of the contract as agreed in the initial contract.